The Principle of Substitution: The Argentine Contribution to Private Sponsorship Schemes? - Rovetta Cortés, Ana Irene (Refuge)

(untitled) (Centre for Refugee Studies, York University, 2023)
This paper provides a critical review of the first private sponsorship scheme to be introduced into Latin America in the last decade, the Syria Program, which has been in place in Argentina since 2014. Though the national and international bodies involved in the initiative (including the International Organization for Migration, UNHCR, and the Global Refugee Sponsorship Initiative) have described it as a good practice, a content analysis of their publications indicates that their interpretations may be overly rosy. Unlike refugee sponsorship schemes that have appeared in other countries, the Argentine private sponsorship program does not complement a public state resettlement scheme but rather appears to replace it.